Stability of Class II malocclusion treatment with the Distal Jet followed by fixed appliances - Ramon Pujols, Sorilee Carlina (2017)
Introduction: This retrospective study aimed to assess the stability of Class II malocclusion treatment with the distal jet, followed by fixed appliances. Methods: Seventy-five cephalograms of 30 subjects, were divided into two groups: the treated group consisted of 15 patients who were evaluated at the pretreatment (T1), posttreatment (T2), and long-term posttreatment (T3) stages. The control group, consisted of 15 subjects with normal occlusion, comparable to the experimental group at the long-term posttreatment period. Intergroup comparison of posttreatment changes was evaluated with t tests. Results: In the posttreatment period, there was no significant change in the anteroposterior positioning the maxilla and mandible in relation to the cranial base. Lower anterior face height had significantly smaller increase in in the treated than in the control group. The maxillary molars in the treated group had significantly smaller vertical development and the mandibular incisors had significantly greater labial tipping and protrusion than the control group. Treatment produced significant improvement in molar relationship and reduction of overbite and overjet, which remained stable in the posttreatment period. There was greater upper lip protrusion in the experimental than in the control group in the posttreatment period. Conclusions: Treatment of Class II malocclusions with the Distal Jet followed by fixed appliances showed long-term stability.